تخطيط وعمارة المعبد اليهودي (التوراة) في ناحية العزير في محافظة ميسان - الدين محسن زاير, صلاح (Al-Adab Journal, 2018)
After establishing the banner of Architecture in 1861 lived in a lot of Jewish families, the city of Missan, it has attracted urbanization that took place in the city center and push them to the stability and build temples in 1884, to perform their religious rituals, the first temple is located in the city center in the locality Qadiriya have been subjected to vandalism in 1990 m, and the other adjacent to the shrine of the prophet of God Uzayr (peace be upon him) in terms of Uzair, to eliminate the benefit of the Castle administratively into brigade architecture, and will be described in this paper to explain the architectural and decorative details for the temple.